Cutaneous mastocytosis: A dermatological perspective. (11th October 2020) - Di Raimondo, Cosimo; Del Duca, Ester; Silvaggio, Dionisio; Di Prete, Monia; Lombardo, Paolo; Mazzeo, Mauro; Spallone, Giulia; Campione, Elena; Botti, Elisabetta; Bianchi, Luca
Abstract: Mastocytosis is a rare disease characterised by expansion and collection of clonal mast cells in various organs including the skin, bone marrow, spleen, lymph nodes and gastrointestinal tract. The prevalence of mastocytosis has been estimated to be one in 10 000, while the estimated incidence is one per 100 000 people per year. Cutaneous mastocytosis is classified into (i) maculopapular cutaneous mastocytosis, also known as urticaria pigmentosa; (ii) diffuse cutaneous mastocytosis; and (iii) mastocytoma of the skin. In adults, cutaneous lesions are usually associated with indolent systemic mastocytosis and have a chronic evolution. Paediatric patients, on the contrary, have often cutaneous manifestations without systemic involvement and usually experience a spontaneous regression. Diagnosis of cutaneous mastocytosis may be challenging due to the rarity of the disease and the overlap of cutaneous manifestations. This short review describes pathogenesis and clinical aspects of cutaneous mastocytosis with a focus on diagnosis and currently available therapies.